Financial markets diffusion patterns. The case of Mexican investment funds - Adam Marszk; Ewa Lechman; Harleen Kaur (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
Exchange traded funds (ETFs) are one of the most influential financial innovations, reshaping the investment funds market in many countries, including Mexico. Due to their similar investment objectives, ETFs are considered substitutes for mutual funds. This paper examines the changes of the investment funds (ETFs and mutual funds) in Mexico over 2002-2012 using a category of the innovation diffusion models, i.e. logistic growth models in order to explore the key development patterns. Descriptions of the selected categories of investment funds are provided in the first section of the article, together with the advantages of ETFs as opposed to mutual funds. Next section presents data sources and methodological framework, with detailed description of the innovation diffusion models applied in the research (based on 3-parametric logistic curve). Sum of assets under management of ETFs and mutual is considered as the size of the total investment funds market. Empirical findings indicate the significant development of the ETF market, both in terms of assets under management and market share. According to the presented estimations, Mexican ETF market development can be described with the logistic growth models, and three characteristic phases of the logistic curve were clearly observable. Predicted ETF market development patterns point towards further increase of market share of ETFs over the next 3-5 years yet the probability of exceeding the level of ca. 20-30% seems low
Keywords: G11; G23; O16; O33; O57; 330; exchange traded funds; mutual funds; diffusion models; financial innovation; Mexico